2021
DOI: 10.1371/journal.pone.0261208
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary comparative study of cortical thickness in HIV-infected patients with and without working memory deficit

Abstract: Purpose Changes in cerebral cortical regions occur in HIV-infected patients, even in those with mild neurocognitive disorders. Working memory / attention is one of the most affected cognitive domain in these patients, worsening their quality of life. Our objective was to assess whether cortical thickness differs between HIV-infected patients with and without working memory deficit. Methods Forty-one adult HIV-infected patients with and without working memory deficit were imaged on a 1.5 T scanner. Working me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
0
1
Order By: Relevance
“…Our study showed that the ReHo value of the right middle frontal gyrus was decreased in ANI patients, while the ReHo value of the left middle frontal gyrus was increased. Unlike previous studies, these seemingly contradictory results may actually reflect compensatory regulation of abnormal brain regions ( 47 ). The middle frontal gyrus is also a cortical area controlling eye movement.…”
Section: Discussioncontrasting
confidence: 83%
“…Our study showed that the ReHo value of the right middle frontal gyrus was decreased in ANI patients, while the ReHo value of the left middle frontal gyrus was increased. Unlike previous studies, these seemingly contradictory results may actually reflect compensatory regulation of abnormal brain regions ( 47 ). The middle frontal gyrus is also a cortical area controlling eye movement.…”
Section: Discussioncontrasting
confidence: 83%